Plato was not a mathematical Platonist - Landry, Elaine M. (Cambridge elements. Elements in the philosophy of mathematics., 2023)
This text shows that Plato keeps a clear distinction between mathematical and metaphysical realism and the knife he uses to slice the difference is method. The philosopher's dialectical method requires that we tether the truth of hypotheses to existing metaphysical objects. The mathematician's hypothetical method, by contrast, takes hypotheses as if they were first principles, so no metaphysical account of their truth is needed. Thus, we come to Plato's methodological as - if realism: in mathematics, we treat our hypotheses as if they were first principles, and, consequently, our objects as if they existed, and we do this for the purpose of solving problems. Taking the road suggested by Plato's 'Republic', this book shows that methodological commitments to mathematical objects are made in light of mathematical practice; foundational considerations; and, mathematical applicability.